System pengendalian intern instansi pemerintah terhadap pengelolaan keuangan di kantor Baitul Mal di Kota Lhoksumawe - Mulyana, Putri; Ropiah, Ropiah; Uswaturrahmi, Uswaturrahmi; Zulkarnaian, Teuku (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study aims to evaluate the internal control system in government agencies in increasing the transparency of financial management at the Baitul Mal Office of Lhokseumawe City. As an institution that manages zakat, infaq, and alms, Baitul Mal plays a strategic role in distributing public funds in a targeted manner. However, challenges in implementing transparency and accountability raise doubts among the public. This research uses literature study method by collecting and analyzing secondary data from various similar studies that have been conducted related to zakat management and internal control system implementation in other zakat institutions. The analysis shows that Baitul Mal has implemented several principles of Good Corporate Governance (GCG), namely transparency, accountability, and responsibility. This implementation has a positive impact on the interest of muzakki to pay zakat. However, there are still constraints in the information system and budget limitations, which hinder the optimization of financial management. The principle of independence has not been fully implemented as Baitul Mal relies on cooperation with the government and third parties in the construction of dhuafa houses.